CREATING ELECTRONIC RESOURCE ETHNO-LINGUISTIC MATERIALS OF THE TATAR LANGUAGE - I. Salimov, Farid; F. Salimov, Rustem (Gênero & Direito, 2019)
We analyze the steps of electronic dictionary creation, built on the basis of ethnolinguistic expeditions of the Institute of Language, Literature and Art Academy of Sciences of the Republic of Tatarstan. Materials were collecting in respect of ethno-cultural archaic dialect zones of Siberia, the Urals region, the Middle and Lower Volga region, densely inhabited by Tatar population. It contains the terminology (ethno-linguistic) dictionary with large amounts of live examples of the Tatar speech, collected in the expeditions. In addition, the created dictionary is associated with the electronic atlas maps of the Tatar folk dialects